Antibacterial extract and active content activity for Erodium cicutarium - Mostafa Qahtan Mostafa; Talib Oid Al-Khesraji; Sirwan Hassan Salih (Tikrit Journal of Pure Science)
Result revealed that all tested extract( hot and cold water) alcoholic (ethanol & methanol) glycosidic and tannic extract at concentration 25, 50, 100 mg/ml were tested of Erodium cicutarium species (Geraniaceae) grown in north and middle of Iraq for their antibacterial (against some gram negative Staphylococcus aureus , Streptococcus lactis &   Gram negative Eschichia coli , Proteus mirabilis pathogenic bacteria) That the methanol extract and extract glycosid an average of 14.540 and 14.530 mm, respectively, are the most effective against the bacteria studied compared to other tested extracts. The results also show that there is variation in the concentration of the active compounds studied depending on the environment (geographical location) Tannin and flavonoid content of aerial plant part and different plant part (aerial part, flower, fruit,  root) was assessed for studied plant using HPLC techniques, and depending on the plant part to the  rutin showed the highest concentration in the vegetative parts compared to other compounds and vegetable segment studied.